Earthquakes and epidemics: the use of metaphors in the Spanish economic press - Ramos Ruiz, Ismael (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Metaphor is one of the most used linguistic resources in economic journalistic discourse. In addition to metaphors about health and medicine, metaphors of natural phenomena are very frequent. Therefore, the objective of this study is to find out what terms about natural phenomena appear in the economic journalistic discourse and what lexical combinations they form. Likewise, the relationship between the conceptual domain of medicine and natural phenomena in the economic journalistic discourse is analyzed.